Absence of Decussation in Optic Pathway Inflammation in Neuromyelitis Optica and Its Implications for Astrocyte Localization. Issue 2 (June 2021) - Harvey, Joshua P.; Hart, Jonathan; Palace, Jacqueline; O'Sullivan, Eoin P.
Abstract : Abstract: A 39-year-old woman presented with acute visual loss in her right eye. Brain and orbit MRI demonstrated T2 hyperintensity along a long section of her right optic nerve, chiasm, and tract with no evidence of decussation of the inflammation. Subsequent seropositivity for the aquaporin 4 antibody confirmed a diagnosis of neuromyelitis optica. Posterior pathway involvement is typical in neuromyelitis optica and supports the hypothesis that the condition is an astrocytopathy. Furthermore, the absence of decussation in the condition may be a function of astrocyte localization within the chiasm.